THE TERTIARY SANDUGA SUITE OF PRIMORYE: AGE AND CORRELATION PROBLEMS - Pavlyutkin B.I.; Petrenko T.I.; Tsarko Y.I. (My University, 2001)
Questions on Tertiary Sanduga suite's toponymy and its section typification are considered. Taking into account the new data on Primorye volcanic plateaus, including the Sanduga suite's stratotype area, the improbability of its correlation with the Ust-Davydovka suite (Lower-Middle Miocene, according to official documents) is shown. The results of sporopollen and diatomic analyses of sedimentary interbasaltic layers as well as the mineralogical and petrochemical study of the Sanduga suite volcanic components in the type section indicate that they are coeval with the Shufansky basalts except for, probably, their uppermost level, which is of Quaternary age. The Sanduga suite basalts were formed during the late Late Miocene - Pliocene. The presence of Quaternary basalts within the Sanduga suite is possible.
Keywords: Pliocene; Quaternary; Miocene; Кайнозой::Четвертичная; Cenozoic::Neogene::Miocene; Cenozoic::Neogene::Pliocene; Cenozoic::Quaternary; Кайнозой::Неоген::Миоцен; Кайнозой::Неоген::Плиоцен